Funding Problems in Educational Institution: Morality and Professionalism Perspectives - Rini, Indra Waspada (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
To achieve these educational goals, adequate facilities and infrastructure are needed so adequate funding is also needed. However, in educational institutions in Indonesia, there are still a number of problems related to education funds and funding. The problems that occur in private schools and government schools are generally different. However, in several ways, there are similarities This study aims to review the problems that occur in education funds and funding in Indonesia. This study belongs to library research or library research with a qualitative research type. Based on this study, it was found that several problems that commonly occur with education funds and funding in Indonesia include misappropriation of BOS funds, lack of funding, and low quality of management of education funds. This problem provides an overview of the morality of the fiduciary, the quality of school performance, and professionalism in education.